2004
DOI: 10.1002/hup.627
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐blind, placebo‐controlled trial of Ginkgo biloba in sexual dysfunction due to antidepressant drugs

Abstract: A triple-blind (investigator, patient, statistician), randomized, placebo-controlled, trial of Ginkgo biloba 240 mg daily was carried out. Following a 1-week control, it was given to 24 patients with sexual impairment due to antidepressant drugs. Efficacy analysis was carried out on eight males and five females on placebo and six males and five females on Ginkgo, completing the full 12 weeks of treatment. Not included were three subjects who dropped out after 6 weeks. A validated, sex (gender)-orientated quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 13 publications
1
28
0
3
Order By: Relevance
“…Thus, beyond the established efficacy of sildenafil for ED, specific improvement in DE could not be distinguished from improvement in erectile function. In other placebo-controlled studies in patients with SSRI-induced sexual dysfunction, Gingko biloba 46 and bupropion 47 were indistinguishable from placebo. In the one study that did show a positive sexual effect of bupropion compared to placebo, the effect was minimal and limited to libido.…”
Section: Management Of Antidepressant-associated Sexual Dysfunctionmentioning
confidence: 74%
“…Thus, beyond the established efficacy of sildenafil for ED, specific improvement in DE could not be distinguished from improvement in erectile function. In other placebo-controlled studies in patients with SSRI-induced sexual dysfunction, Gingko biloba 46 and bupropion 47 were indistinguishable from placebo. In the one study that did show a positive sexual effect of bupropion compared to placebo, the effect was minimal and limited to libido.…”
Section: Management Of Antidepressant-associated Sexual Dysfunctionmentioning
confidence: 74%
“…In a clinical trial study conducted by Wheatley in the United Kingdom to determine the effect of Ginkgo biloba on sexual function in men and women aged at 18-65 yrs under depression treatment, taking 240 mg Ginkgo biloba extract caused no change in sexual activity improvement (29). Failure to consist with our study could be due to the differences in health status of the subjects because their samples were men and women treated for depression, while our samples were only healthy postmenopausal women.…”
Section: Discussionmentioning
confidence: 87%
“…Following positive early reports of its efficacy in this area, there have now been two placebo-controlled RCTs of G. biloba as a possible antidote to antidepressant-induced sexual dysfunction. Neither trial has shown a benefit of the use of G. biloba [27,28]. Both were small in size, with a total number of only 61 participants over the two studies, and included both men and women.…”
Section: Ginkgo Bilobamentioning
confidence: 92%